Darier White disease - A Amatya; D Karn; E Aryal; R Makaju; A Shakya; A Priyadarshinee (Nepal Journal of Dermatology, Venereology & Leprology)
Darier’s disease was described inependently by Darier and White in 1989 AD. Reported prevalence varies from 1/100,000 in Denmark to 1 in 30- 35,000 in northern England and Scotland.1 Darier’s disease has been reported from other parts of the world, however,there has been no reported cases in Nepal. It is an inherited autosomal dominat disease characterized by dark crusty lesions over the seborrheic areas of the skin. We are reporting a case of Darier’s disease in a Nepalese patient who developed skin leison’s over his face and body at the age of 12 years. We took skin punch biopsy from the leisons, which showed findings suggestive of Darier’s disease. Our case was treated with isotrerenoin and topical keratolytics. He responded with the given treatment within two weeks of therapy.